Problems of development of ICT competence of students of natural science training - Nurgazinovа Гульбаршын (Рroblems of engineering and professional education, 2023)
This article describes the difficulties in the development of the competence of professional teachers of the future science and creation science, as well as the brief reasons for this, as well as the ways to solve this problem.